The Effect of Capital Structure, Firm Size, and Profitability on Firm Value with Investment Decisions as Moderating - Wijayaningsih, Shinta; Yulianto, Agung (Universitas Negeri Semarang, 2021)
The purpose of this study is to examine the effect of capital structure, firm size, and profitability on firm value with investment decisions as moderating. The population of this study was 49 various industrial sector manufacturing companies listed on the IDX in 2016-2019. Sampling using purposive sampling technique, in order to obtain a sample of 22 companies with 72 units of analysis. Data analysis was performed using the Moderated Regression Analysis (MRA) test. The results showed that profitability had a positive effect on firm value, while capital structure did not affect firm value and firm size had a negative effect on firm value. Investment decisions are able to strengthen the effect of profitability on firm value but are not able to strengthen the effect of capital structure and firm size on firm value. The conclusion of this study is that company value will increase if it has high profitability because the greater the profit the company gets, the better the company’s performance, and the company value will decrease when the larger the company size means that the bigger the company, the more difficult it is to control and supervise by company management. Meanwhile, the right investment decision increases the company’s chances of making a profit, thereby strengthening the effect of profitability in increasing firm value. Keywords: Firm Value; Capital Structure; Company Size; Profitability; Investment Decisions